A Scoping Review of Compensation and Benefits Practices Among Selected Asian Countries - Caren Campos Sasan; John Lemuel G. Buntigao (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2026)
As Asian economies continue to diversify and integrate into the global market, organizations across the region face increasing pressure to design compensation and benefits systems that are both competitive and responsive to local cultural, economic, and regulatory conditions. This study presents a scoping review of compensation and benefits practices across selected Asian countries, examining how cultural, economic, institutional, and regulatory factors shape the design and implementation of reward systems. Using Arksey and O’Malley (2005) scoping review framework, the study synthesized findings from peer-reviewed journals, government reports, and grey literature to map existing knowledge, identify thematic patterns, and highlight gaps in the field. Results show significant variation in compensation structures driven by national labor policies, collectivist or individualist cultural orientations, economic development levels, and industry-specific demands. Common trends include the rising emphasis on strategic compensation, performance-based rewards, employee well-being, and digital HR innovations. However, disparities persist, particularly in labor protection, migrant worker welfare, and equitable benefits. The review also notes the limited cross-country comparative research in Asia, indicating the need for more empirical studies on compensation effectiveness and cultural fit. Overall, the findings underscore the importance of context-sensitive, flexible, and culturally aligned compensation frameworks to support fair labor practices and organizational competitiveness in the Asian region.